Photovoltaic and Supercapacitor performance of SnSe nanoparticles prepared through co-precipitation method. (24th August 2022) - Dar, Mohd Arif; Govindarajan, D.; Batoo, Khalid Mujasam; Hadi, Muhammad; Dar, G. N.
ABSTRACT: In this paper, we report Tin Selenide (SnSe) nanoparticles preparation through co-precipitation method and characterised by UV–Vis spectroscopy, scanning electron microscopy, Fourier transforms infrared spectroscopy, X-ray diffraction, EDX spectrum, photovoltaic and Supercapacitor performance. XRD patterns indicate that the prepared SnSe nanoparticles exist in the orthorhombic phase. The SEM and TEM image show that nanoparticles exhibit spherical shapes with high agglomeration. The UV-Visible spectrum recorded in the range of 200–800 nm, show peaks at 260 nm, 300 nm, and 350 nm while direct energy bandgap lies between 1.4 eV and 1.8 eV and indirect energy bandgap lies between 1.5 eV to 1.6 eV. The obtained SnSe counter electrodes (CEs) showed good electrocatalytic activity in the redox reaction of the I − /I3 − . The Dye-sensitised solar cells (DSSC) of SnSe with molar ratios (1:1), (2:1), and (3:1) as showed good photovoltaic performances in comparison to platinium (Pt) counter electrode (CE). The higher specific capacitance value 1335 F/g of SnSe (3:1) electrode compare to the SnSe (1:1) and (1:2) electrodes proves the stability of SnSe (3:1) for supercapacitor performance.